Penerapan Model Project Based Learning untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa Kelas IV pada Pembelajaran PKn - AP, Nurfaizah; Aras, Latri; Ramdhani, Aulifia Kirana (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
This study aims to describe the application of the Project Based Learning model to improve students' creative thinking skills in Civics learning in class IV of SD Inpres Karunrung Makassar City. The approach used is a qualitative approach with a type of Classroom Action Research (PTK) research consisting of 4 main activities, namely planning, action, observation, and reflection. The focus of this research is to improve the creative thinking skills of fourth grade students of SD Inpres Karunrung Makassar City. Data collection using observation sheets, evaluation tests in each cycle and documentation. Data analysis used is qualitative. The results of this study indicate that the Project Based Learning model on students' creative thinking skills during the implementation of cycle I and cycle II that the research results obtained in cycle I were in the category of less (L) or not creative and there was an increase in cycle II which was in the good (G) or very creative category and achieved the predetermined indicators. The conclusion of this study is that by applying the Project Based Learning (PjBL) model can improve students' creative thinking skills on the material of the Unitary State of the Republic of Indonesia in Class IV SD Inpres Karunrung Makassar City.